Growth and inhibition of Thiobacillus ferrooxidans in relation to acid drainage from Witwatersrand gold mine sand dumps - Conradie, Judith M.(Judith Magdalena),1958- (Stellenbosch : Stellenbosch University, 2012)
Thesis (M. Sc.) -- University of Stellenbosch, 1984.